2020
DOI: 10.1126/sciadv.abc9959
|View full text |Cite
|
Sign up to set email alerts
|

Titanium isotopes constrain a magmatic transition at the Hadean-Archean boundary in the Acasta Gneiss Complex

Abstract: Plate subduction greatly influences the physical and chemical characteristics of Earth’s surface and deep interior, yet the timing of its initiation is debated because of the paucity of exposed rocks from Earth’s early history. We show that the titanium isotopic composition of orthogneisses from the Acasta Gneiss Complex spanning the Hadean to Eoarchean transition falls on two distinct magmatic differentiation trends. Hadean tonalitic gneisses show titanium isotopic compositions comparable to modern evolved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 117 publications
1
29
0
Order By: Relevance
“…To summarize, our work shows that Ti coordination has a major influence on Ti isotopic fractionation during magmatic differentiation and we can successfully reproduce the trend documented in tholeiitic rocks, but our model predicts a larger Ti isotopic fractionation in calc-alkaline rocks than what is measured. Once the controls on Ti isotopic fractionation are ascertained, this system can potentially be used to reconstruct the history of oxide crystallization of igneous rocks for which a full magmatic differentiation series is not available and possibly tease out the effects of assimilation and magma mixing. , It may also yield new insights into magma differentiation early in Earth’s history and compositions relevant to partial melting and differentiation in the Archean (e.g., rutile and TTGs).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To summarize, our work shows that Ti coordination has a major influence on Ti isotopic fractionation during magmatic differentiation and we can successfully reproduce the trend documented in tholeiitic rocks, but our model predicts a larger Ti isotopic fractionation in calc-alkaline rocks than what is measured. Once the controls on Ti isotopic fractionation are ascertained, this system can potentially be used to reconstruct the history of oxide crystallization of igneous rocks for which a full magmatic differentiation series is not available and possibly tease out the effects of assimilation and magma mixing. , It may also yield new insights into magma differentiation early in Earth’s history and compositions relevant to partial melting and differentiation in the Archean (e.g., rutile and TTGs).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Arc magmatism and calc-alkaline magma differentiation are fundamental processes in the establishment of felsic continental crust. Titanium (Ti) isotopes provide unique insights into magmatic differentiation processes, as the δ 49 Ti composition of magmatic rocks increases with increasing silica content, reflecting the history of partial melting and Fe–Ti oxide crystallization. The Ti isotopic composition of fine-grained terrigenous sediments (shales) has been used to conclude that, as far back as 3.5 Ga, the composition of the crust exposed to weathering comprised a large fraction of felsic rocks, implying that subduction processes were likely operating before that time . Subsequent work demonstrated that Ti isotopes fractionated distinctly in plume and island arc settings, ,, suggesting that Ti isotopes may provide insights into the geodynamic setting responsible for the formation of the continental crust …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5; see also supplementary Figure S4). As Saharan dust is derived predominantly from Proterozoic granitoids in the Tuareg shield, it is not surprising that its δ 49/47 Ti matches that of calc-alkaline rocks and tonalitetrondhjemite-granodiorite (TTG) suites (Figure 7; Millet et al, 2016;Greber et al, 2017;Aarons et al, 2020;Hoare et al, 2020). Moreover, δ 49/47 Ti of Saharan dust overlaps with the upper end of Proterozoic to presentday marine shales, which display rather limited variability with time (Figure 7; Greber et al, 2017;Deng et al, 2019).…”
Section: Ti-zr Isotope Composition Of Saharan Dust and Its Protolithmentioning
confidence: 98%
“…The <63 µm suspended sediment fraction (uncertainties are 1s) is a good match for this Nile-derived component. Millet and Dauphas, 2014;Millet et al, 2016;Greber et al, 2017;Deng et al, 2018;Deng et al, 2019;Aarons et al, 2020;Hoare et al, 2020). B) δ 94/90 Zr compared with literature data for basalts, granitoids (≥65 wt.% SiO 2 ) and sediments (Inglis et al, 2018;Inglis et al, 2019;Feng et al, 2020;Tian et al, 2020).…”
Section: Figure Captionsmentioning
confidence: 99%